Annotations in scholarly editions and research : functions, differentiations, systematization - Nantke, Julia; Schlupkothen, Frede (Berlin : De Gruyter, 1974)
Annotations in Scholarly Editions and Research: Functions, Differentiation, Systematization is a collection of essays exploring the concept of annotations in various academic fields. Edited by Julia Nantke and Frederik Schlupkothen, this book brings together the insights from an international conference held at the University of Wuppertal in 2019. The publication examines different approaches to annotation in the humanities and technical sciences, highlighting their similarities and differences. It aims to provide a systematic understanding of the role of annotations in scholarly editions and research, emphasizing their importance in the context of digitalization.
Includes index.
Keywords: Annotations in scholarly editions and research; Annotations in the humanities; Annotations in the technical sciences; Annotations and digitalization